2015
DOI: 10.1097/iop.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Quantification on Nasolacrimal Silastic Stents After Dacryocystorhinostomy

Abstract: This is the first study to report the quantification of biomass on lacrimal stents. The presence of biofilms on lacrimal stents after DCR is a common finding but this need not necessarily translate to postoperative clinical infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Although biofilms on the surface of the lacrimal stents is a well-known phenomenon and may increased the probability of infection,21, 22, 23 in the presence of the biofilms the culture may be negative 24, 25. Murphy J and colleagues reported that biofilm was present in nasolacrimal stents after 4 weeks, however we suggested that it's better to postponed the intraocular surgery until the removal of silicone tube.…”
Section: Discussionmentioning
confidence: 73%
“…Although biofilms on the surface of the lacrimal stents is a well-known phenomenon and may increased the probability of infection,21, 22, 23 in the presence of the biofilms the culture may be negative 24, 25. Murphy J and colleagues reported that biofilm was present in nasolacrimal stents after 4 weeks, however we suggested that it's better to postponed the intraocular surgery until the removal of silicone tube.…”
Section: Discussionmentioning
confidence: 73%
“…One common approach is simple thresholding, which is effective when there are differences in the pixel intensity value between biofilm and background. Many studies investigating biofilm removal have used thresholding to segment images of biofilm from photographs and light microscopy images, however typically manual thresholding has been employed81726, which is subjective leading to large errors and making intra-operator reproducibility impossible. Other studies using automatic thresholding have failed to specify the exact method of segmentation or validate its accuracy71621.…”
mentioning
confidence: 99%
“…Once infection occurs, to treat infection and prevent recurrences, the prosthetic medical devices must be removed and antibiotics must be used at stronger doses or more often. It has been reported that if lacrimal stents are left longer than 1 month, biofilms may influence postoperative healing and the ultimate outcome [ 34 ]. Our results also support the use of prophylactic antibiotics after surgery.…”
Section: Discussionmentioning
confidence: 99%